Ecophysiological Features of Polar Soil Unicellular Microalgae1. Issue 2 (22nd January 2020) - Shukla, Satya P.; Kvíderová, Jana; Adamec, Lubomír; Elster, Josef
Abstract : Due to their ecological, physiological, and molecular adaptations to low and varying temperatures, as well as varying seasonal irradiances, polar non‐marine eukaryotic microalgae could be suitable for low‐temperature biotechnology. Adaptations include the synthesis of compounds from different metabolic pathways that protect them against stress. Production of biological compounds and various biotechnological applications, for instance, water treatment technology, are of interest to humans. To select prospective strains for future low‐temperature biotechnology in polar regions, temperature and irradiance of growth requirements ( Q 10 and Ea of 10 polar soil unicellular strains) were evaluated. In terms of temperature, three groups of strains were recognized: (i) cold‐preferring where temperature optima ranged between 10.1 and 18.4°C, growth rate 0.252 and 0.344 · d −1, (ii) cold‐ and warm‐tolerating with optima above 10°C and growth rate 0.162–0.341 · d −1, and (iii) warm‐preferring temperatures above 20°C and growth rate 0.249–0.357 · d −1 . Their light requirements were low. Mean values Q 10 for specific growth rate ranged from 0.7 to 3.1. The lowest Ea values were observed on cold‐preferring and the highest in the warm‐preferring strains. One strain from each temperature group was selected for PN and RD measurements. The PN :RD ratio of the warm‐preferring strains was less affected by temperature similarly as Q 10 and Ea. For future biotechnological applications, the strains with broad temperature tolerance (i.e., the group of cold‐ and warm‐tolerating and warm‐preferring strains) will be most useful.